Incorporating the mature students voice and lived experiences into continuous quality improvement - Lubbe, J.C.; Wolvaardt, J.E.; Turner, A.C. (South African Journal of Higher Education, 2020)
Improving academic quality requires feedback from students since they have specific insight in their lived educational experience. Most institutions assess educational experience by evaluating individual modules. Few institutions collectively review evaluation data from multiple modules or explore this data for evidence of curriculum transformation. The University of Pretoria developed four curriculum transformation drivers and the School of Health Systems and Public Health developed and implemented 19 transformation-related statements. We revised the standard end-of-module evaluations to explore student experiences regarding the implementation of these drivers. 45 modules were reviewed. The quantitative data were analysed in Excel. Qualitative data were analysed using an inductive approach with open-coding. We generated categories and themes before comparing these to the curriculum transformation drivers. Four major themes emerged from the qualitative data: reflecting the ‘what’, ‘why’, ‘when’, ‘where’, ‘how’ and ‘who’ of the student experience. Categories and subcategories were explored and linked to the quantitative results. The results show that the students valued their educational experience and felt valued as students. The students’ voices provided a rich source of data regarding curriculum transformation and included detailed suggestions for quality improvement. Our study presents substantive evidence of authentic educational and philosophical intentions that were realised in practice.